Safety and efficacy of cell‐free and concentrated ascites reinfusion therapy against cirrhotic ascites in comparison with malignancy‐related ascites. Issue 11 (22nd August 2021) - Ito, Tetsuya; Hanafusa, Norio; Soneda, Noriko; Isoai, Ayako; Kobayashi, Ryosuke; Torii, Naoko; Kato, Michio
Abstract: Background and Aim: Cell‐free and concentrated ascites reinfusion therapy (CART) has been performed against cirrhotic ascites, one of the most common complications seen in patients with decompensated cirrhosis. The aim of this study is to investigate its safety and efficacy, and differences in clinical profiles from CART against malignancy‐related ascites with different pathological background. Methods: The present investigation involved a sub‐analysis of data obtained from a prospective observational study of CART performed at 22 centers. The condition of each procedure, therapeutic options, laboratory data, performance status, dietary intake, and abdominal circumference of participants were analyzed. Clinical parameters were compared between before and after CART, with or without albumin infusion, and also primary diseases including cirrhosis and malignant disease. Results: Between January 2014 and January 2015, a total of 48 and 275 CART procedures were performed in patients with cirrhosis and malignancies. In cirrhotic patients, serum albumin concentration increased significantly in groups both with and without concomitant albumin infusion ( P = 0.002 and P = 0.023), and no significant difference in CART interval was seen between these groups ( P = 0.393). CART interval was not significantly different between cirrhosis and malignancy groups ( P = 0.334). Dietary intake significantly improved after CART in both groups ( P = 0.043 and P < 0.001). Adverse events were with no clinical significance as observed in patients with malignancies. Conclusions: Cell‐free and concentrated ascites reinfusion therapy was performed safely and effectively in patients with ascites related to decompensated cirrhosis and offers the potential efficacy to maintain plasma colloid osmotic pressure after paracentesis as well as in patients with malignancy.